Pelayanan Pendidikan yang Prima melalui Learning Management System (LMS) Berbasis Moodle untuk Mewujudkan Sekolah Efekitf pada Masa Pandemi Covid-19 di SMP Negeri 1 Kebumen - Martiyono ,; Maesaroh ,; HM. Iim Wasliman; Sri Handajani (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2022)
The aims of this study are (1) to describe and analyze excellent educational services through a Moodle-based Learning Management System (LMS) at SMP Negeri 1 Kebumen and (2) to find out the impact and results for realizing effective schools during the Covid-19 pandemic. The research method used is a qualitative research method. Sources of data used are resource persons, namely principals, teachers, students, and parents of students as well as documents. Data collection methods used are observation, documentation, and interviews. Data analysis used descriptive qualitative techniques, with the validity of the data using triangulation of data collection techniques and sources. Excellent education services through the Moodle-based Learning Management System (LMS) at SMP Negeri 1 Kebumen with steps (1) planning, by forming a work team, preparing Standard Operating Procedures (POS), preparing facilities and infrastructure, and preparing development instruments, (2 ) socialization and capacity building to teachers and administration, students, school committees and parents, (3) implementation trials, (4) implementation, and (5) monitoring, evaluation and follow-up. The application of the Moodle Learning Management System (LMS) at SMP Negeri 1 Kebumen can create an effective school, which is characterized by (1) efficient use of inputs, (2) effectiveness of learning implementation and education management, both planning, socialization, testing, implementation, and monitoring, evaluation, and follow-up), (3) output productivity, namely learning and accountable education management, and (4) outcome relevance, namely implementation, involvement, and student satisfaction in Learning From Home (BDR). Keywords: Learning Management System (LMS), Moodle, Covid-19 Pandemic, and